2013
DOI: 10.1038/nature11837
|View full text |Cite
|
Sign up to set email alerts
|

The genomic signature of dog domestication reveals adaptation to a starch-rich diet

Abstract: The domestication of dogs was an important episode in the development of human civilization. The precise timing and location of this event is debated and little is known about the genetic changes that accompanied the transformation of ancient wolves into domestic dogs. Here we conduct whole-genome resequencing of dogs and wolves to identify 3.8 million genetic variants used to identify 36 genomic regions that probably represent targets for selection during dog domestication. Nineteen of these regions contain g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
827
3
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 823 publications
(873 citation statements)
references
References 35 publications
29
827
3
14
Order By: Relevance
“…This finding is not a surprise and is consistent with the rapid evolution of genes in the nervous systems of other domestic animals, which has collectively been attributable to behavioral shifts that accompany domestication [14][15][16][17][18]. In addition, functional enrichment analysis of genes in regions with the top 1% XP-EHH scores revealed that many candidate genes related to the npg www.cell-research.com | Cell Research nervous system were over-represented in the following Human Phenotype Ontology (HPO) categories: abnormality of the nervous system (31 genes), abnormality of the central nervous system (30 genes), and cognitive impairment (25 genes) (P < 0.05) (Supplementary information, Table S8).…”
Section: Positively Selected Genes In Domestic Chickens Compared Withsupporting
confidence: 68%
See 1 more Smart Citation
“…This finding is not a surprise and is consistent with the rapid evolution of genes in the nervous systems of other domestic animals, which has collectively been attributable to behavioral shifts that accompany domestication [14][15][16][17][18]. In addition, functional enrichment analysis of genes in regions with the top 1% XP-EHH scores revealed that many candidate genes related to the npg www.cell-research.com | Cell Research nervous system were over-represented in the following Human Phenotype Ontology (HPO) categories: abnormality of the nervous system (31 genes), abnormality of the central nervous system (30 genes), and cognitive impairment (25 genes) (P < 0.05) (Supplementary information, Table S8).…”
Section: Positively Selected Genes In Domestic Chickens Compared Withsupporting
confidence: 68%
“…Dogs also harbor weaker visual acuity compared to their wild ancestors, however, in contrast to chickens, there was no evidence for positive selection in visionrelated genes in previous studies [14][15][16]. Vision is important in birds for survival [58], but other sensory abilities including hearing and smell, might play more important roles in mammals.…”
Section: Discussionmentioning
confidence: 90%
“…These results support our hypothesis that comparison of recently domesticated population with its wild founder population facilitates the discovery of candidate loci for traits under strong deliberate and accidental selection in the new hatchery environment. In dogs, phenotypes that vary most conspicuously among recently derived breeds, including size, limb length, coat color, coat texture, behavior, diet, skeletal morphology, and physiology have been used to identify the genomic regions that possess strong signatures of recent selection and contain major candidate genes (Akey et al., 2010; Axelsson et al., 2013; Pollinger et al., 2005; Von Holdt et al., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Domestication is the evolutionary process of genetic adaptation of wild animal populations to environmental conditions created deliberately or accidently by humans. This process can involve changes in morphological, physiological, behavioral, and life history traits (Mignon‐Grasteau et al., 2005) and began at least 15,000 YBP, when dogs were domesticated to facilitate hunting or to guard human settlements (Axelsson et al., 2013; Braastad & Bakken, 2002; Frantz et al., 2016). Subsequently, from 8,000 to 10,000 YBP, pigs, sheep, goats and cattle were domesticated as a source of food (Craig, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Domestication is considered to have generated behavioural changes, such as reduced fearfulness and aggressiveness towards humans (Serpell and Duffy, 2014), and regarding sociability and cognition (Marshall-Pescini and Kaminski, 2014). Axelsson et al (2013) identified 19 regions in the genome that were believed to have been under selection as an effect of domestication, and that contained genes of relevance to brain function. Serpell and Duffy (2014) noted that what makes the dog unique compared to other domesticated species is that dog selection has primarily been on behaviour.…”
Section: Dog Behaviour Is Importantmentioning
confidence: 99%